Unlocking Reading Comprehension: Empowering English Language Learners through Main Idea Identification Strategies - Pranoto, Yohanes Heri; Inharjanto, Anselmus; Ismadi, Florentinus Heru; Clara, Catharina; Leovani, Ega (Wacana Akademika: Majalah Ilmiah Kependidikan, 2023)
English reading can be challenging for language learners, as they often require a high level of comprehension and critical thinking skills. Developing a strategy for identifying the main idea of each paragraph can be a helpful tool for improving reading proficiency. This study investigated the effectiveness of teaching students to identify the main idea of each paragraph in order to empower their English reading skills. The study employed an experiment with a pre and post-test design, with 22 students from St. Paul Minor Seminary participating in the study. The pre and post-test design was used to measure the effectiveness of the intervention. The pre and post test results were analyzed with a dependent sample t-Test to determine if there was a significant improvement or not. The study found that identifying the main idea can be helpful in improving reading comprehension and motivation, as the students are better able to understand the plot. Overall, the study provided valuable insights into the use of specific strategies for enhancing reading skills in language learners.